Pengaruh Praktik Pengalaman Lapangan Dan Prestasi Belajar Terhadap Minat Menjadi Guru Akuntansi - Wahyu Sholekah; Supri Wahyudi Utomo; Elly Astuti (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2021)
This study aims to determine the effect of field experience practice (PPL) and learning achievement on interest in becoming a teacher. The population of this study were 96 students of the 2016 Accounting Education Study Program who had taken internship 2 and apprenticeship 3 (PPL) courses. The sampling technique was carried out with saturated samples. The data collection technique was carried out by using a questionnaire and the students' final GPA. The data analysis method used is multiple linear regression. The results showed that Field Experience Practices (PPL) had a positive effect on student interest in becoming teachers and learning achievement had no effect on student interest in becoming teachers. Experience when participating in PPL will make students have insight and knowledge about the world of work so that students know how the real teaching process in class is and can find out how the teacher's activities are at school, this makes students have a high interest in becoming teachers because students are already gain experience and knowledge when participating in PPL activities. Learning achievement does not affect the interest in becoming a teacher because the competencies that are owned are more focused on other professions such as accountants and do not lead to the teaching profession. This can be based on several factors such as motivation, attitudes and interests.